Experimental feasibility study on low-temperature differential stirling engines with water spray heat transfer - Jang, S.-J.; Lee, Y.-P.; Sim, K. (Korean Society of Mechanical Engineers, 2014)
This paper presents the results of an experimental feasibility study on low-temperature differential Stirling engines with water spray heat transfer. The water spray enhances the efficiency of the heat transfer from heat sources to the engine and reduces the performance degeneration due to the dead volumes of conventional heat exchangers. A test Stirling engine was developed and an experiment was conducted to determine the characteristics for the initial start-up, steady-state operation, and power output for various flow rates and temperatures of hot supply water. The test results showed that larger flow rates led to reductions in the minimum working temperature of the hot water at start-up. During a series of steady-state operations, higher flow rates and temperatures increased the working speed. Furthermore, the work per cycle and power output were also increased. Eventually, the test Stirling engine had a power level of 0.05 W. Based on this, further research will be conducted to obtain a higher power output and investigate various applications. ？ 2014 The Korean Society of Mechanical Engineers.
Keywords: Flow rate; Heat transfer; Metal drawing; Planning; Spraying; Temperature; Thermoelectric power; Differential Stirling engine; Feasibility studies; Heat Transfer enhancement; Low temperature heat sources; Low temperatures; Steady-state operation; Work per cycle; Working temperatures; Stirling engines